HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PEMERIKSAAN HIV DAN SIFILIS DI PUSKESMAS MEDAN JOHOR TAHUN 2025 - Putri Inda Aulia; Suryani; Rismahara Lubis; Dodoh Khodijah (Poltekkes Kemenkes Medan, 2025)
HIV and Syphilis are still hot issues in society, especially among pregnant women who are very susceptible to sexually transmitted infections (IMS), especially HIV and Syphilis. The prevalence rate in Indonesia for HIV and Syphilis reaches 0,39%. HIV reaches 1,7% and Syphilis reaches 2,5% in pregnant women. This is due to the lack of knowledge and insight about HIV and Syphilis, which causes negative attitudes such as fear and unwillingness to undergo HIV and Syphilis examinations because they feel unimportant. This study aims to determine the relationship between knowledge and attitudes of pregnant women with HIV and Syphilis examinations. This study uses a quantitative method with a cross-sectonal research design. This type of research is quantitative analytic. The number of respondents was 50 pregnant women in TM 1 or Tm 3 who underwent pregnancy examinations at the Medan Johor Health Center, which used the Total Sampling technique. Data were obtained using quetionnaires and laboratory test. The results of the study showed that out of 50 respondents, 30 respondents were in the category of good knowledge about HIV and Syphilis. Meanwhile, 39 respondents had a positive attitude toward HIV and Syphilis examinations and 11 respondents had a negative attitude and one respondent whose test results were positive. The results of the statistical test using Chi- Square showed a significance result of p = 0,304 (p > 0,05), so it can be concluded that there is no relationship between the knowledge and attitudes of pregnant women with HIV and Syphilis examinations